Problems And Opportunities Of The Beekeeping System In Uzbekistan - Rustamov Axmad Jumayevich; Komilova Nilufar Karshiboyevna (Zien Journals, 2025)
This article explores the current status and development potential of beekeeping in Uzbekistan, focusing on its regional, climatic, and agro-economic dimensions. Beekeeping has gained strategic importance in the country, with the establishment of the “Uzbekistan Beekeepers Association” in 2017, which led to key reforms such as tax exemptions, soft loans (UZS 36 billion via Aloqabank), and technology introduction. In 2023, Uzbekistan produced 31,500 tons of honey a 16% increase from the previous year. Meanwhile, in 2020, production stood at 21,410 tons. However, average honey yield per hive remains low, below 20 kg
Keywords: Beekeeping in Uzbekistan; Honey production; Climate change